Clinical Factors and Outcomes When Real-World Heart Teams Overruled STS Risk Scores in TAVR Cases - Jackson M. King; Morgan T. Black; Ruyun Jin; Gary L. Grunkemeier; Branden R. Reynolds; Brydan D. Curtis; Robert W. Hodson; Erika A. Strehl; Sameer A. Gafoor; Matthew D. Forrester; Emily J. Cox; Michael E. Ring (Journal of Interventional Cardiology)
Objectives. This study was conducted to determine why heart teams recommended transcatheter aortic valve replacement (TAVR) versus surgical AVR (SAVR) for patients at low predicted risk of mortality (PROM) and describe outcomes of these cases. Background. Historically, referral to TAVR was based predominately on the Society of Thoracic Surgeons (STS) risk model’s PROM >3%. In selected cases, heart teams had latitude to overrule these scores. The clinical reasons and outcomes for these cases are unclear. Methods. Retrospective data were gathered for all TAVR and SAVR cases conducted by 9 hospitals between 2013 and 2017. Results. Cases included TAVR patients with STS PROM >3% (n = 2,711) and ≤3% (n = 415) and SAVR with STS PROM ≤3% (n = 1,438). Leading reasons for recommending TAVR in the PROM ≤3% group were frailty (57%), hostile chest (22%), severe lung disease (16%), and morbid obesity (13%), and 44% of cases had multiple reasons. Most postoperative and 30-day outcomes were similar between TAVR groups, but the STS PROM ≤3% group had a one-day shorter length of stay (2.5 ± 3.4 vs. 3.5 ± 4.7 days; p≤0.001) and higher one-year survival (91.6% vs. 86.0%, p=0.002). In patients with STS PROM ≤3%, 30-day mortality was higher for TAVR versus SAVR (2.0% vs. 0.6%; p<0.001). Conclusions. Heart teams recommended TAVR in patients with STS PROM ≤3% primarily due to frailty, hostile chest, severe lung disease, and/or morbid obesity. Similar postoperative outcomes between these patients and those with STS PROM >3% suggest that decisions to overrule STS PROM ≤3% were merited and may have reduced SAVR 30-day mortality rate.